Collusion with private and aggregate information - Jim Y. Jin (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
This paper considers three linear asymmetric oligopoly models with (i) a representative consumer, (ii) horizontal differentiation and (iii) vertical differentiation. We show that firms could maximize the joint-profit only based on private and aggregate information. They can choose the “correct“ colluding prices without knowing the demand or profit function. The collusive outcome is a natural focal point despite firms are asymmetric. Collusion can be incentive compatible even though individual actions (prices) are not observed. – – Der Beitrag untersucht drei linear asymmetrische Oligopol-Modelle mit (i) einem repräsentativen Verbraucher, (ii) horizontaler Differenzierung und (iii) vertikaler Differenzierung. Es wird gezeigt, daß Firmen in der Lage sind, den Gesamtprofit allein auf der Grundlage privater und gemeinschaftlicher Information zu maximieren. Sie können zur ,,richtigen“ Absprache des Preises gelangen, ohne die Nachfrage- oder Gewinn-Funktion zu kennen. Die Absprache stellt einen natürlichen Gleichgewichtspunkt dar, ungeachtet asymmetrischer Verhältnisse. Die Absprache kann anreizkompatibel sein, auch wenn individuelle Aktionen (Preise) nicht beobachtet werden.
Keywords: 330